Mauritius : Recent Economic Developments and Selected Issues. (IMF Staff Country Reports; Country Report ;, 1997)
This Recent Economic Developments and Selected Issues paper on Mauritius highlights that the real GDP growth for the country during 1993/94-1995/96 averaged about 4.1 percent, compared with 6.0 percent for the preceding three years. The decline in GDP growth, especially in 1994/95, was largely on account of the adverse impact of Cyclone Hollanda, which hit the island in February 1994. The negative effects of the cyclone were the most pronounced in the sugar sector, where output in 1994 declined by 12 percent compared with 1993.